Life Cycle Assessment Analysis of Corrugated Carton Box Production Process to Measure Eco-Efficiency Level - Fatmawati, Erliansa; Ernawati, Dira; Dewi, Sinta (Journal La Multiapp, 2025)
The production of carton boxes is an energy-intensive process that generates various contaminants, polluting water and air, and affecting both ecology and human health. This study focuses on the environmental impact during the carton box production process at PT XYZ, aiming to calculate and analyze the environmental impact while measuring the eco-efficiency level of the production process. The research method employed in this study is quantitative descriptive, with primary data sources consisting of interviews, while secondary data includes company reports. Data were processed using SimaPro software and the Eco Indicator 99 method. Eco-efficiency measurement was conducted using the Life Cycle Assessment approach. The results indicate that the production of 1 ton of carton boxes generates an environmental impact of 315 Pt, with the largest contributions coming from the corrugating, folding, and customer delivery stages. The eco-cost value was IDR8,922,503, yielding an eco-efficiency index of 1.34, indicating that the production process is environmentally friendly and economical. However, the eco-efficiency ratio of 25.6% is still considered low, necessitating improvements in energy efficiency and emission reduction. Recommended improvements include substituting fossil fuels with renewable energy, selecting environmentally friendly suppliers, and replacing or modifying machinery to enhance efficiency and reduce emissions.